New technologies in pasture and grazing management in the face of climate change perspectives - Prudencio, Marcelo Falaci (2022)
The search for sustainable livestock farming has been the focus of several researches in Brazil and worldwide, in face of climate change. Livestock production is mostly explored in pastures in Brazil. It is estimated that a large part of these pastures presents some kind of degradation, as a result of its incorrect management. With this degradation, besides reducing productivity, there is loss of soil organic matter and CO2 emission to the atmosphere, with a reduction in carbon sequestration by the pasture. Consequently, there is the release of excess enteric methane, which occurs in the digestive process of ruminants, by fermentation of fibrous and poor quality food ingested by these animals from this pasture. Several studies propose new technologies to mitigate greenhouse gases, with intensive pasture management, processing and conservation of forage to reduce particle size and increase digestibility. Recovery and renovation of pastures, using integrated production systems with grain, forest, and forage production. Implementation of pasture with forage in suitable environments and use of grasses with better leaf/stem ratio. Use of rotational grazing with height control of animals entering and leaving each forage species in order to produce a better and more digestible forage. With this, reduce the precursors of greenhouse gases to mitigate the possible effects on climate change.